The effect of team building programs on athletic performance in collegiate female soccer players - Tsuchiya, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Previous research has explored the benefits of team-building (TB) interventions on social support in the team environment and improving athletes` performance (Tsuchiya, 2001). In this study, a TB program was developed based on the theory of a structured group-encounter technique (Kokubu,1992), and was used by a collegiate women`s soccer team at a national championship tournament. The purpose of this study was to examine whether the program would positively influence the team`s performance at the tournament. Methods The participants in this study were 33 student-athletes from a collegiate women's soccer team. Subjects were divided into a competitive group (starting line-up and substitute, N=18) and a non-competitive group (N=17). Both groups` members were willing to participate in the TB program to improve their psychological condition as a team member. The team had broken through first-round matches several times, but never won the final tournament. Unfortunately, the prime players suffered injury and the overall team competence rapidly declined during the year. Based on that situation, an original TB intervention program was developed as a structured group-encounter that consisted of psychological skill training and intensive group experience. The program included six sessions, each one intended to facilitate performance enhancement and to activate social support of the team members. The program started one month before the tournament and was conducted by a certified sport psychology consultant from the Japanese Society of Sport Psychology. The questionnaire was composed of the athletic social support inventory (Tsuchiya, 2001) and the team competence scales. Each member answered the same questionnaire on two occasions: pre-intervention (Pre) and post-intervention (Post). Results / Discussion A two (groups) × two (times) mixed-model analysis of variance yielded significant interaction showing that the social support score of the competitive group increased Post (F(1,31)=9.31, p<.01). Also, regarding team competence scores, a significant difference was found between Pre and Post results in both groups. This finding indicated that the program contributed to improving feelings of competence for team members (F(1,31)=4.47, p<.05). In addition, the coaches reported that improvement was observed both in team cohesion and in the members` attitudes toward practice. All members reached personal performance goals in the first round. Furthermore, the team defeated the reigning champion in the final tournament and won the national championship. It was concluded that the TB program would have a positive effect on the team environment and performance.